The inflatable thymus herniation of the normal mediastinal thymus: A case report and review of the literature. (April 2016) - Stuut, Marijn; van Zwieten, Gusta; Straetmans, Jos M.; Lacko, Martin; Stumpel, Constance T.R.M.
Abstract: Anterior neck masses in young children can be a diagnostic challenge for otolaryngologists and radiologists. We present a rare case of herniation of normal mediastinal thymus in a four-year-old girl. Additional medical features as an inguinal hernia and trochlear nerve paresis raised the question whether there is a causal relationship or an association. A connective tissue disorder could not be diagnosed as possible causal factor to the abnormal movement of the mediastinal thymus. Awareness and recognition of this benign phenomenon is important in order to avoid unnecessary biopsy or surgery. Diagnosis can be confirmed by ultrasonography. Magnetic Resonance Imaging might be valuable in order to obtain more information about the extension of the mass.